EKSTRAKSI ETANOL DENGAN FLUIDA SUPERKRITIK : PEMODELAN KESETIMBANGAN FASA SISTEM BERASOSIASI - Nyoman Widiasa, I
Abstract: Supercritical fluid extraction (SCFE) has been proven as an efficient separation method for some specific industrial applications. Moreover, the SCFE is extensively used in the other applications, such as for concentrating fermentation products, chromatography analysis, environmental, chemical reaction, petroleum and materials processing. Advantages of applying SCFE are less energy consumption; ^ t on-toxic solvent. Solvent recovery is much simple than conventional extraction, i.e. by adjusting small change of pressure or temperature. Ethanol is an important substance. The main difficulty of separation ethanol from fermentation product is the relatively great affinity between ethanol and water. Further, product concentration is limited by its azeotropic property. The use of SCFE is an alternative process to cope the problem and makes SCFE becaome an attractive research field. The objectives of this research are to study phase equilibrium model for systems involving associating components such as H20-C2H50H, The research also study effect of temperature and pressure to ethanol solubility and selectivity in CO2 supercritic. Equations of state of SRK, PR, and PT incorporated with several type of mixing rules were used in phase equilibrium modelling. The capability of these equations were tested with vapor-liquid equlibrium data of this work and of available literatures. Regression of interaction parameters utilized Simplex method while solution of non-linear equation system made use Powel Dogleg Hibrid-Rosenbrock algorithm that written in FORTRAN language. The results of the study suggests that optimal condition for supercritical extraction of ethanol from aqueous solution is in the range pressure and temperature 80-120 bar and 313-330 K respectively. The study also found that it is difficult to produce ethanol above its azeotropic concentration by using just single stage extraction. For same mixing rule, each of equations of state have different interaction parameter value. Interaction parameter are also reported for that systems and their values depend on temperature. For further studies, experimental and modelling studies should be focussed at other solvent which have entrainment effect.